FACTUAL CONTENT OF HISTORY IN THE FILM FETIH 1453: MUATAN FAKTA SEJARAH DALAM FILM FETIH 1453 - Hidayat, Muhammad Naufal; Ismail, Sanusi (Indonesian Journal of Islamic History and Culture, 2023)
This research aims to identify the historical facts present in the film Fetih 1453. It uses historical methods, including heuristic, verification, interpretation, and historiography. The research findings indicate that the film Fetih 1453, directed by Faruk Aksoy, is based on historical facts. The film is set during the Ottoman Empire era, specifically during the rule of Sultan Mehmed II, depicting the story of the Ottoman conquest of Constantinople. The fictional elements present in some characters do not alter the main storyline of the film, which revolves around the conquest of Constantinople. Other aspects examined in the research include the historical facts presented in the film Conquest 1453. Faruk Aksoy portrays historical facts through numerous scenes in the film. The film successfully provides historical information, such as the second ascent of Sultan Mehmed II, the creation of large cannons, the construction of fortresses in Rumelia, the transportation of ships over hills, and the conquest of Constantinople. This film can be used as a reference to understand the depiction of the Ottoman attack on Constantinople through a historical approach, allowing for a sequential examination of events.